Chromosome fragility in nasopharyngeal carcinoma (NPC) - Yee, Peter Han Chung (Universiti Malaysia Sarawak (UNIMAS), 2007)
Nasopharyngeal carcinoma (NPC) is reported to be associated with Epstein-Barr virus (EBV) infection as well as genetic alterations in the nasopharyngeal epithelium. These include common deletions at 3p, 9p, 11q, 13q and 14q; and additions at 1q, 3q, 8q, 11q and 12p. The 11q23 which contains the Mixed Lineage Leukaemia (MLL) gene appears to be the common region of deletion. Till date, the mechanism of chromosome rearrangements (addition or deletion) is unknown. However, apoptosis induced chromosome break within the MLL gne have been reported in the leukaemia cells. Thus, the aim of this project is to elucidate the role of apoptosis /EBV-induced apoptosis which may lead to chromosomal rearrangement in NPC. Materials and Methods: NPC cell line was treated with apoptotic stimuli and purified DNA fragments were separated on agarose gel.